A construção de uma memória do regime militar: uma análise do filme 'O que é isso companheiro?' - Lima, Indiara da Silva (2012)
This study aims to analyze how the movie O que é isso companheiro? created a memory from when Brazil was governed by a military regimen, focusing on the attitudes of groups of armed young people against the government. The movie was based on the namesake book of the militant Fernando Gabeira, published at the end of 1970s. The book was written in a time marked by an intense production of memoirs about that period of history and in the midst of political opening. The film was released almost 20 years later, in 1997, amid a movement of revival of film production in Brazil and in an appropriate format to the movies industry. This work is intended to combine the analysis of fictional construction based on a melodramatic narrative structure array with external variables related not only to production but also to the historical and social contexts in which the film was produced.